SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN LOMBOK TIMUR DENGAN METODE RAPID APPLICATION DEVELOPMENT (RAD) - Febriansyah, Lalu Dwiky Indrajid; Ratnasari, Dwi; Agitha, Nadiyasari (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2025)
Libraries are essential tools for supporting education and learning activities. However, libraries in some areas still use manual systems to manage book data and other services. East Lombok Regency is one such area that requires an updated library information system to enhance the efficiency and effectiveness of its services. Observations at the East Lombok Regency Library and Archives Office revealed that library services are still conducted manually, with librarians using notebooks to record book borrowings. This manual system poses challenges in managing borrowed and returned books, especially as the East Lombok Library and Archives Office permit schools nationwide to borrow books. To address these issues, researchers employed the Rapid Application Development (RAD) method to design the information system. This method was chosen for its ability to shorten development time compared to traditional methods. The newly developed library information system aims to assist schools facing a shortage of books, particularly in remote village areas. The application of RAD successfully increased development efficiency and improved the system's effectiveness in meeting the library's operational needs. Furthermore, the system reduced dependence on manual processes, enhanced data accessibility, and simplified library data management. These improvements enable more optimal library services for the residents of East Lombok. This success is supported by the results of a questionnaire, with 80% of respondents agreeing that the system effectively meets their needs.